Disease outcomes and biomarkers of progression in smouldering Waldenström macroglobulinaemia. (2nd August 2021) - Zanwar, Saurabh; Abeykoon, Jithma P.; Ansell, Stephen M.; Gertz, Morie A.; Colby, Colin; Larson, Dirk; Paludo, Jonas; He, Rong; Warsame, Rahma; Greipp, Patricia T.; King, Rebecca L.; Thompson, Carrie A.; et al.
Summary: Patients with asymptomatic/smouldering Waldenström macroglobulinaemia (SWM) have a variable risk of progression to active WM. Our study evaluated 143 patients with SWM consecutively seen between January 1996 and December 2013. With a median [95% confidence interval (CI)] follow‐up of 9·5 [8·1–11·5] years, the cumulative rate of progression was 11% at 1 year, 38% at 3 years and 55% at 5 years. On multivariate analysis, haemoglobin (Hb) ≤123 g/l [risk ratio (RR) 2·08; P = 0·009] and β2 ‐microglobulin (β2 M) ≥2·7 µg/ml (RR 2·0; P = 0·01) were independent predictors of a shorter time‐to‐progression (TTP) to active WM. Patients with myeloid differentiation factor 88 wild type ( MYD88 WT ) genotype ( n = 11) demonstrated a trend toward shorter TTP [median (95% CI) 1·7 (0·7–8·7) vs. 4·7 (2·4–7·7) years for the MYD88 L265P cohort, n = 42; P = 0·11]. The presence of C‐X‐C chemokine receptor type 4 ( CXCR4 ) mutation ( n = 29) did not impact the TTP (median: 3 years for CXCR4 WT vs. 5·6 years for CXCR4 MUT, P = 0·34). The overall survival (OS) for patients with SWM (median: 18·1 years) was comparable to an age‐, sex‐ and calendar year‐matched USA population (median: 20·3 years, P = 0·502). In conclusion, Hb and β2 M at diagnosis represent independent predictors of progression to active WM. Comparable survival of SWM and a matched USA population argues against pre‐emptive intervention in this patient population.